HUBUNGAN PERAN ORANG TUA DALAM PENGELOLAAN PEMBERIAN SUSU FORMULA BOTOL DENGAN KEJADIAN KARIES GIGI PADA BALITA DI TK DHARMA WANITA PERSATUAN WAUNG SIDOARJO - Suparlan, Lila Lusiana; Sutomo, Hadi; Verawati, Dessi (LPPM STIKes Bahrul Ulum Jombang, 2018)
Bottle formula feeding in infants less precise, such as bedtime and not cleaning the teeth can cause dental caries. The purpose of this study to determine the relationship of parent role in the management of bottle feeding formula with the incidence of dental caries in infants in kindergarten Dharma Wanita Persatuan Waung Village Krembung District Sidoarjo Regency. This research uses correlational analytic design with cross sectional approach. The population in this study amounted to 60 people mother and toddler. The sampling technique used purposive sampling with 33 respondents who fulfilled the inclusion criteria. Data collection using the parent role questionnaire and dental caries observation sheet def-t. Based on Spearman Rank test obtained correlation coefficient of 0.615 with 0.000 <α (0.01) means there is a parent role relationship in the management of bottle feeding formula with the incidence of dental caries in infants. It is expected that parents increase the role in the management of bottle feeding formula for toddlers avoid dental caries.